(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Learning disability is a classification including several areas of functioning in which a personhas difficulty learning in a typical manner usually caused by an unknown factor or factors. While learningdisability and learning disorder are often used interchangeably, the two differ. Learning disability is whena person has significant learning problems in an academic area. These problems however, are notenough to warrant an official diagnosis. Learning disorder, on the other hand is an official clinicaldiagnosis whereby, the individual meets certain criteria as determined by a professional (psychologist,pediatrician, etc). The unknown factor is the disorder that affects the brain ability to receive and processinformation. Another problem in learning process is learning disabilities, in propose research weexamine two types of learning disabilities infrastructural and neurological this both disabilities are notpresent in handicapped categories and this learning disabilities mostly present in rural student due tolack of facility and educational environment.